Arsenic residues from historic gold extraction, Snowy River, Westland, New Zealand. Issue 1 (2nd January 2021) - Kerr, Gemma; Craw, Dave
ABSTRACT: The Snowy River processing site was used to extract gold for the large historic Blackwater mine, Westland, between 1906 and 1938, and then abandoned. The site is now one of the best-preserved historic gold-processing localities, and access has been enhanced for visitors. The site has some high arsenic (As) concentrations on the surface, with some spots exceeding 40 wt% As. A variety of As-bearing minerals occurs along the former processing stream, from primary sulphides (arsenopyrite, pyrite) at the upstream end to arsenolite (As2 O3 ) and scorodite (FeAsO4 .2H2 O) formed by the roasting of ore materials at the downstream end. Weathering over the past century of sulphide residues and some of the arsenolite has yielded more scorodite and some Ca arsenates. Minor authigenic As sulphide precipitates have formed on rotting wood. Arsenolite is principally distributed near to the roaster site, and this is the most soluble and potentially toxic mineral on site. Despite the locally abundant arsenolite, only minor As is mobilised into nearby waters.